Heavy Metal Accumulation and Mycorrhizal Association of the Common Agroforestry Crops in the Ultramafic Soils of Dinagat Islands, Philippines - Aribal Lowell G; Mancile Danilo S; Marin Rico A; Bruno Angela Grace T (International Journal of Life Sciences, 2018)
Common Agroforestry crops in the ultramafic soils of Santo Niño, Cagdianao, Dinagat Islands were studied to determine their heavy metal accumulation and mycorrhizal association. Three Agroforestry farms were sampled for the crops such as coconut, sweet potato, and banana. On each farm, plant parts were collected separating the edible and the non-edible parts such as shoots and roots and were tested for accumulation of nickel and chromium via atomic absorption spectrophotometry. Soil samples within the rhizosphere of the crops were also collected for mycorrhizal studies. Results showed that all Agroforestry crops accumulated nickel and chromium on roots and shoots above the normal range at 0.05-10 mg/kg, however, only banana has nickel concentration exceeding the normal range of 5-25 mg/kg. For the edible parts, all Agroforestry crops have nickel and chromium concentration above the safety limits of 0.0028 and 0.3 mg/kg body weight per day for nickel and chromium, respectively. Only sweet potato has shoot/root quotient or translocation factor greater than one for both nickel and chromium which was 12.73 and 11.09, respectively, thus considered as hyperaccumulator species. Six genera of mycorrhiza were identified in all crops with Glomus as the most abundant followed by Acaulospora, Scutellospora, Entrophospora, Sclerocystis, and Gigaspora.